SLOWING EXTRUSION TECTONICS: LOWERED ESTIMATE OF POST-EARLY MIOCENE SLIP RATE FOR THE ALTYN TAGH FAULT - Yue Y.; Ritts B.D.; Graham S.A.; Wooden J.L.; Gehrels G.E.; Zhang Z. (My University, 2004)
Determination of long-term slip rate for the Altyn Tagh fault is essential for testing whether Asian tectonics is dominated by lateral extrusion or distributed crustal shortening. Previous slip-history studies focused on either Quaternary slip-rate measurements or pre-Early Miocene total-offset estimates and do not allow a clear distinction between rates based on the two. The magmatic and metamorphic history revealed by SHRIMP zircon dating of clasts from Miocene conglomerate in the Xorkol basin north of the Altyn Tagh fault strikingly matches that of basement in the southern Qilian Shan and northern Qaidam regions south of the fault. This match requires that the post-Early Miocene long-term slip rate along the Altyn Tagh fault cannot exceed 10 mm/year, supporting the hypothesis of distributed crustal thickening for post-Early Miocene times. This low long-term slip rate and recently documented large pre-Early Miocene cumulative offset across the fault support a two-stage evolution, wherein Asian tectonics was dominated by lateral extrusion before the end of Early Miocene, and since then has been dominated by distributed crustal thickening and rapid plateau uplift.
Keywords: ALTYN TAGH FAULT; POST-EARLY MIOCENE SLIP RATE; XORKOL BASIN; PROVENANCE ANALYSIS; SHRIMP ZIRCON DATING; Quaternary; Miocene; Cenozoic::Quaternary; Кайнозой::Четвертичная; Кайнозой::Неоген::Миоцен; Cenozoic::Neogene::Miocene